New excavations at Canteen Kopje, Northern Cape province, South Africa: a techno-typological comparison of three earlier Acheulean assemblages with new interpretations on the Victoria West phenomenon - Leader, George Michael (My University, 2014)
The site of Canteen Kopje in Barkly West, South Africa, has provided the archaeological record with an invaluable collection of Earlier Stone Age artefacts. An alluvial deposit approximately 1km from the modern Vaal River, the site contains an abundance of artefacts. A 2007 – 2009 excavation in Pit 6 has provided an assemblage of over 15,000 artefacts that has been dated by cosmogenic nuclide burial method. Three distinct assemblages show technological changes through time of the earlier Acheulean industrial complex. The youngest industry, the Prepared Core Technology Assemblage, is dated to 1.2 ± .07 Ma and contains Victoria West prepared core technology. Beneath it is the Organised Core Assemblage which is void of Victoria West prepared core technology but contains cores that demonstrate more organised knapping techniques in the form of asymmetrical control. This assemblage is dated to 1.51 ±0.8 Ma. Finally, the underlying Basal Early Acheulean Assembage lacks both prepared cores and organised cores and is >1.51 Ma in age. The abundance of large angular clasts of andesite in the area made multiple knapping strategies effective for the manufacture of large flakes. A technological sequence in the knapping strategies has emerged in this excavation, from simple cores to organised cores and finally prepared cores. The older technologies clearly display the roots of prepared core technology in the asymmetrical control of the organised knapping methods. The overall success of the knapping strategies prior to the appearance of the Victoria West industry in the Canteen Kopje archaeological record creates questions as to why more complex strategies might have been implemented over time. Analysis of the assemblages from the Pit 6 excavation fails to provide a clear technological explanation within the empirical data as to why this change occurs. This research therefore argues that the Victoria West prepared core knapping strategy is a localized stone age culturally motivated knapping tradition.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 2014.
Keywords: Excavations (Archaeology); Archaeology - Methodology.; Mesolithic Period - South Africa - Northern Cape.; Northern Cape (South Africa) - Antiquities.; Stone Age - South Africa - Canteen Kopje.